2021
DOI: 10.3389/fpubh.2021.689820
|View full text |Cite
|
Sign up to set email alerts
|

Meager Perception of Preconception Care Among Women Desiring Pregnancy in Rural Areas: A Qualitative Study Using Focus Group Discussions

Abstract: Background: India has the second-highest number of under-five deaths in any country in the world. WHO and the Government of India recommended the rollout of preconception care (PCC) to reduce maternal and child mortality. However, very few countries, including India, have started a comprehensive package of PCC services. It implies that women, mainly from rural and tribal areas, are not aware of PCC. PCC has been rolled out through the government health system in two blocks of Nashik district in Maharashtra sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…As can be seen in Table 1 , all included articles were from 2018 and beyond, and four were from 2021. Of the eight selected studies, five were conducted in low- to middle-income countries (Ethiopia, Indonesia, India, and Nigeria) [ 13 , 15 , 17 - 19 ], and three were from high-income countries (the United States, Japan, and Australia) [ 12 , 14 , 16 ]. These findings indicated the increased interest in PCC research following a better understanding of PCC’s importance for women’s and children’s health across the globe.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As can be seen in Table 1 , all included articles were from 2018 and beyond, and four were from 2021. Of the eight selected studies, five were conducted in low- to middle-income countries (Ethiopia, Indonesia, India, and Nigeria) [ 13 , 15 , 17 - 19 ], and three were from high-income countries (the United States, Japan, and Australia) [ 12 , 14 , 16 ]. These findings indicated the increased interest in PCC research following a better understanding of PCC’s importance for women’s and children’s health across the globe.…”
Section: Resultsmentioning
confidence: 99%
“…Although research in Ethiopia showed that many pregnant women understood human immunodeficiency virus screening, family planning, and hypertension screening, only a few were aware of folic acid and iron consumption and hepatitis B screening, as PCC information was usually provided by health workers only during antenatal visits [ 17 ]. A qualitative study in India also reported that of 76 women (aged 15 to 39 years) who participated in focus group discussions, most were well acquainted with the basic concepts of PCC, such as nutrition pre-pregnancy and the effects of tobacco and alcohol effects, but only a few were aware of the need of good mental health, PCC programs, sexually transmitted infections, and the effect of chronic medical conditions; furthermore, 50% had an unplanned pregnancy and most did not access PCC services [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is a part of a comprehensive intervention study that broadly aims to reduce low birth weight and preterm births by addressing the known risk factors in the preconception period. The knowledge and behavior among women desiring pregnancy regarding preconception care are reported elsewhere ( 41 ).…”
Section: Introductionmentioning
confidence: 99%
“…Planning of pregnancy not only by the couple but the family as such is necessary. The dominant role of the mother-in-law cannot be (11) neglected . The estimated proportion of unintended (12) pregnancies may be about 50% .…”
mentioning
confidence: 99%